Study of Acid Whey Fouling after Protein Isolation Using Nanofiltration - Marjana Simonič; Zorka Novak Pintarič (Membranes, 2021)
In this paper, nanofiltration (NF) of acid whey after isolation of proteins was studied. Two membranes were tested: NF-99 (Alfa Laval) and DL (Osmonic Desal). Based on previous measurements that determined the highest efficiency in separating lactic acid and lactose whey, the pH was adjusted to 3. First, the most appropriate transmembrane pressure (TMP) was determined based on the highest flux measured. The TMP range was 5–25 bar for the DL membrane and 10–30 bar for the NF-99 membrane. The temperature was kept at 4 °C using a thermostat. The mechanisms of membrane fouling were investigated. The Hermia models and the modified Tansel model were applied to study the fouling mechanism and to determine which membrane would foul earlier and more severely, respectively. The most suitable TMP was determined at 20 bar. Despite the 1.4 times higher flux of the sample at DL, the fouling rate was higher when NF-99 was used. The results showed that the Tansel model is suitable for predicting the fouling time of protein-isolated whey by nanofiltration.